Effect of moisture on tensile properties of oil palm empty fruit bunch (EFB) unsaturated polyester composites - Mohamad Ali, S. (Universiti Malaysia Sarawak, UNIMAS, 2008)
This research addressed to the oil palm empty fruit bunch fibre as the potential fibre for fibre reinforced polymer composites. An oil palm empty fruit bunch reinforced polyester composites have been fabricated in a random orientation. The specimens are categorized according to its fibre volume fraction (10%, 15% and 20%), the type of surface treatment (untreated, NaOH and Silane), and moisture content (1%, 2%, 3% and 4%). A moisture absorption test and tensile test according to ASTM D3039 standard has been carried out in order to determine the moisture content and understand the moisture effects of the composite under tension. The results showed that the untreated composites with 20% fibre volume fraction and 1% of moisture content had the best mechanical properties in terms of tensile strength, Young’s modulus and energy at break. Furthermore, it also verified that the increment of moisture content in specimen with the same fibre volume fraction and surface treatment reduced the tensile strength.